Membangun kepercayaan nasabah melalui strategi branding yang kuat dalam perbankan syariah - Mashudi, Fajar Asnif (Maliki Interdisciplinary Journal, 2025)
This research aims to analyze the influence of Islamic branding strategies on customer trust in sharia banking. Literature studies show that Islamic branding, which adopts sharia values ​​such as honesty and accountability, is able to attract the interest of Muslim consumers and build trust. Several previous studies also show a positive relationship between brand image, perceived quality, and customer trust. Elements of effective Islamic branding include marketing communications that are in accordance with Islamic values, quality sharia services, and a physical environment that reflects Islamic identity. Apart from that, the role of customers as active parties in supporting the development of sharia banking is also an important factor. In conclusion, Islamic branding is a crucial strategy in building customer trust in sharia banking. By implementing sharia values ​​consistently, sharia banking can create competitive advantages and achieve sustainable growth.